1982
DOI: 10.1177/070674378202700510
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Gender-Role Behaviour in Children Attending Traditional and Non-Traditional Day-Care Centres

Abstract: Using a sex-typed free-play task and the Draw-a-Person test, the gender-role behaviour of children attending a day-care centre whose staff adhered to a "non-sexist" child-rearing philosophy was compared to the gender-role behaviour of children attending a more traditional day-care center. Parental provision of sex-typed and neutral toys and approval of cross-sex role behaviour was also assessed. On both measures, the two groups of children showed culturally typical patterns of gender-role behaviour. The parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…For example, it has long been observed that the sexes differ in the extent to which they display sex-typical behaviors; when there is significant between-sex variation, it is almost always the case that girls are more likely to engage in masculine behaviors than boys are likely to engage in feminine behaviors (e.g., Cole, Zucker, & Bradley, 1982;Sandberg, Meyer-Bahlburg, Ehrhardt, & Yager, 1993). Thus, the base rates for cross-gender behavior, at least within the range of normative variation, may well differ between the sexes.…”
Section: Sex Differences In Referral Ratesmentioning
confidence: 98%
“…For example, it has long been observed that the sexes differ in the extent to which they display sex-typical behaviors; when there is significant between-sex variation, it is almost always the case that girls are more likely to engage in masculine behaviors than boys are likely to engage in feminine behaviors (e.g., Cole, Zucker, & Bradley, 1982;Sandberg, Meyer-Bahlburg, Ehrhardt, & Yager, 1993). Thus, the base rates for cross-gender behavior, at least within the range of normative variation, may well differ between the sexes.…”
Section: Sex Differences In Referral Ratesmentioning
confidence: 98%